Rare Cases of Pediatric Vasoactive Intestinal Peptide Secreting Tumor With Literature Review: A Challenging Etiology of Chronic Diarrhea - Yeh, Pai-Jui; Chen, Shih-Hsiang; Lai, Jin-Yao; Lai, Ming-Wei; Chiu, Cheng-Hsun; Chao, Hsun-Chin; Chen, Shih-Hsin; Wu, Ren-Chin; Wang, Chao-Jan; Chen, Chien-Chang (Frontiers in Pediatrics, 2020)
Vasoactive intestinal peptide (VIP) secreting tumor (VIPoma) is a rare disease, presenting with profuse diarrhea, electrolyte imbalance, and possibly fatal outcome. The diagnosis and treatment are challenging, while no consensus guideline of management is available. The pediatric incidence remains unclear. This study comprises of two pediatric case reports from a tertiary center and a literature based case series, investigating the characteristics among children. The two reported cases both presented with severe diarrhea and laboratory abnormalities, including electrolyte imbalance and elevated plasma VIP level. Case one received several imaging investigations, partial pancreatectomy, octreotide, and everolimus, reflecting her complicated and refractory course. Case two underwent total excision of suprarenal ganglioneuroblastoma and the clinical response was significant. In both cases, varied degree of symptomatic control, reduced plasma VIP level, and correction of electrolyte imbalance were achieved. A literature review-based case series analyzed forty-five pediatric cases retrieved from the PubMed database until December 31st, 2019. Demographics, clinical features, diagnostic modalities, treatments and outcomes were presented.